Réponses

2013-04-20T22:30:35+02:00

a) 6t²-18t

= 3t(t-6)

=3t(t-6)=0

 

3=0

 

t-6=0

t=6

2013-04-20T23:03:57+02:00

a) 6t(t-3)=0  ; si t=0 ou t-3=0 donc t=3

b) (x-2)(3x+5)=0 ; si x-2=0    ou  3x+5=0

                                      x=2      ou   3x=-5; x= -5/3

c)[(y-3)+2][(y-3)-2]=0

    (y-1)(y-5)=0   ; si y-1=0  ou y-5=0

                                   y=1     ou y=5

d)36x²+12x+1-49+56x+16x² = 52x²+68x-48 = 4(13x²+17x-12) , je sais pas si cest ca là!

  Si (6x+1)=0  ou 7+4x=0

         6x=-1      ou   4x=-7

            x=-1/6  ou     x=-7/4